2016
DOI: 10.3390/ijerph13030329
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Sand Fly Populations and Leishmania infantum Infection Rates in an Irrigated Village Located in Arid Central Tunisia

Abstract: The current spread of zoonotic visceral leishmaniasis (ZVL) throughout arid areas of Central Tunisia is a major public health concern. The main objective of this study is to investigate whether the development of irrigation in arid bio-geographical areas in Central Tunisia have led to the establishment of a stable cycle involving sand flies of the subgenus Larroussius and Leishmania infantum, and subsequently to the emergence of ZVL. Sand flies were collected from the village of Saddaguia, a highly irrigated z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
4
29
0
Order By: Relevance
“…Recently, in a study conducted in the center of Tunisia, it was demonstrated that Ph. perniciosus was predominant in arid bioclimatic zones and irrigated areas [42,51].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, in a study conducted in the center of Tunisia, it was demonstrated that Ph. perniciosus was predominant in arid bioclimatic zones and irrigated areas [42,51].…”
Section: Discussionmentioning
confidence: 98%
“…Phlebotomus papatasi, the vector of L. major in Tunisia, is known to be abundant in arid and Saharan regions. Aridity seems to be a limiting factor for its distribution and it was described especially in non-irrigated areas [18,[42][43][44][45]. However, the high number of Ph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, no L. infantum strain has been isolated from this phlebotomine sand fly species yet. Also, L. infantum DNA was detected from a P. langeroni, P. longicuspis, P. perfiliewi, P. papatasi, and Sergentomyia minuta using molecular tools [45,46]. However, neither parasite isolation from these sand flies species nor L. infantum isoenzymatic identification were carried out in Tunisia yet to confirm their role as vector of L. infantum taxon.…”
Section: Transmission Cyclementioning
confidence: 99%
“…However, the vector hosts of the two other zymodemes MON-24 and MON-80 are still unknown (Figure 5). Recently, L. infantum DNA was detected in the sand flies mid gut of the Larroussius (P. langeroni, P. longicuspis, P. perfiliewi) and Phlebotomus (P. papatasi) subgenera as well as the Sergentomyia genus (S. minuta) [45,46]. However, neither parasite isolation from these sand flies species nor L. infantum isoenzymatic identification were carried out in Tunisia yet to confirm their role as vector of L. infantum zymodemes.…”
Section: Transmission Cyclementioning
confidence: 99%